The Millennium Development Goals, Capacity Building, and the Role of the IMF - Hakura, Dalia; Nsouli, Saleh (Washington, D.C. : International Monetary Fund, 2003)
The Millennium Development Goals (MDGs) represent a global commitment to improve economic and social conditions in low-income countries. Capacity building is key to promoting higher economic growth, which, in turn, is an important prerequisite for making progress toward the MDGs. This paper uses the UNDP's emerging framework for capacity building to show how the IMF supports capacity building at the individual, organizational, and the system level, thereby contributing to the efforts of countries to meeting the MDGs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Country; Developing Country; IMF Institute; Training; WP; United Arab Emirates